Research–Practice–Collaborations in International Sustainable Development and Knowledge Production: Reflections from a Political-Economic Perspective - Katja Bender (The European Journal of Development Research, 2022)
The cooperation between researchers and practitioners during the different stages of the research process is promoted as it can be of benefit~to both society and research supporting processes of 'transformation'. While acknowledging the important potential of research–practice–collaborations (RPCs), this paper reflects on RPCs from a political-economic perspective to also address potential unintended adverse effects on knowledge generation due to divergent interests, incomplete information or the unequal distribution of resources. Asymmetries between actors may induce distorted and biased knowledge and even help produce or exacerbate existing inequalities. Potential merits and limitations of RPCs, therefore, need to be gauged. Taking RPCs seriously requires paying attention to these possible tensions—both in general and with respect to international development research, in particular: On the one hand, there are attempts to contribute to societal change and ethical concerns of equity at the heart of international development research, and on the other hand, there is the relative risk of encountering asymmetries more likely.
Keywords: 330; Knowledge co-production; International sustainable development; Research-practice-collaborations; Collective action; Interests; Power